Generation of recombinant SNAP-tag based antibody fusion proteins for immunotherapy of acute myeloid leukemia (AML) - Molope, Gomolemo Atlegang (Department of Pathology, 2025)
Acute Myeloid Leukemia (AML) remains a significant challenge to cure. In Africa, Leukemia is among the ten most prevalent cancers. The lack of an updated registry, medical technologies that provide timely diagnosis, and convenient access to appropriate treatments would result in an alarming increase in incidence and fatality rates in the near future. Patients with AML are often treated with chemotherapy, stem cell transplantation, or targeted therapy in an effort to achieve long-term remission and a longer lifespan. However, treatment provision is not always readily available in economically-constrained settings, as in many African countries. Furthermore, while a variety of therapies have been developed for AML, these often result in severe side effects, highlighting the urgent need for advanced medical interventions. Addressing these challenges necessitates innovative therapeutic approaches, such as recombinant antibody-drug conjugates (ADCs), which may offer targeted treatment options with reduced toxicity compared to traditional therapies. In this study, we focused on developing target-specific next-generation recombinant ADCs to improve treatment outcomes. Immunotherapy, especially the use of ADCs, has demonstrated significant promise in treating leukemia and several other cancers. Targeting CD33 and CD45, which are both highly expressed in AML, by using novel recombinant ADCs offers a promising therapeutic approach. This proof-of-concept study was conducted to show that protein engineering can be used to locally produce immunotherapeutics with potentially fewer adverse effects for the treatment of AML. Recombinant ADCs comprised of single-chain fragment variables (scFv) fused to a self labelling human protein called SNAP-tag were generated. SNAP-tag was used for site-specific conjugation to O6 -benzylguanine (BG) derivatives to demonstrate functionality against overexpressed and therapeutically relevant AML antigens CD33 and CD45. The scFv component of each recombinant ADC was designed in silico and cloned into mammalian expression vectors for production of recombinant SNAP fusion proteins (FPs). Purification of the SNAP FPs was performed using immobilized metal affinity chromatography (IMAC). SDS PAGE and Western blot analysis were used to characterise the fusion proteins, facilitated by an N-terminal 10x Histidine (His) tag. The αCD33(scFv)-SNAP-Alexa 488 and αCD45(scFv)- SNAP-Alexa 488 fusion proteins were assessed for cell surface binding on AML cell lines using flow cytometry. The recombinant ADCs; αCD33(scFv)-SNAP-AURIF and αCD45(scFv)- SNAP-AURIF were then utilized in an XTT cell viability assay to evaluate targeted cell killing. The successful design and functionality of these AML-specific recombinant ADCs were demonstrated in this study. This was illustrated by the SDS-PAGE gels results from the initial IMAC purification showing full-length protein of αCD33(scFv)-SNAP, and αCD45(scFv)- SNAP-tagged fusion proteins at around 51.8 kDa and 52.5 kDa, respectively. Both αCD33(scFv)-SNAP-Alexa 488 and αCD45(scFv)-SNAP-Alexa 488 showed antigen dependent binding, which was confirmed by flow cytometry. Furthermore, the cytotoxicity assays demonstrated the dose-dependent killing of target AML cells by both αCD33(scFv)- SNAP-AURIF and αCD45(scFv)-SNAP-AURIF. The comparable binding capacity and cytotoxic potential of these generated immunoconjugates to their specific antigenic targets exhibited their hope for use as therapeutic interventions that will advance the field of immunotherapeutics for AML in the future. With the possibility of also using this form of therapy together with other existing AML therapies, there would be chances of enhanced cancer cell death at lower doses of drugs, thus minimizing dose-dependent adverse effects experienced by patients. In conclusion, encouraging local production of such innovative treatments that are comparable to those sold and made widely available to patients in fully developed countries, can help lessen the impact of the disparities in access to quality healthcare that exist throughout the world as a result of the notably large differences in socioeconomic status. This will in turn also have an overall positive impact on the African economy as less money will be required to purchase and import AML treatments. Instead, the local production of these immunotherapeutics will promote a cost-saving strategy while ensuring that the need for AML patients' access to essential treatments is still met.